Risk of pneumonia in patients with insomnia: A nationwide population-based retrospective cohort study - Chia-Ling Lin; Ta-Chun Liu; Chi-Hsiang Chung; Wu-Chien Chien (Elsevier, 2018)
Evidence is lacking regarding whether insomnia increases the risk of infectious disease. Accordingly, the present study examined the risk of pneumonia in patients with insomnia.This study was a population-based retrospective cohort study on a cohort of 8061 patients with insomnia and a control cohort of 16,112 patients (matched by age, sex, and year of diagnosis) from the Taiwan National Health Insurance Research Database for the 2000-2010 period.Overall incidence of pneumonia was 50.6 per 1000 person-years in the insomnia cohort, which was significantly higher than that in the control cohort (30.9 per 1000 person-years). Overall, the insomnia cohort exhibited a higher risk of pneumonia (HR = 2.43; CI, 2.24-2.62). By age group, the risk of pneumonia was significantly higher in the insomnia cohort for those aged ≤40 years (HR = 3.23, CI: 1.38-7.57), 41-65 years (HR = 2.62, CI: 2.07-3.32), and >65 years (CI: 2.21-2.61).Compared with the controls, the insomnia cohort exhibited a higher risk of pneumonia, particularly in young adults. Keywords: Insomnia, Pneumonia, Retrospective cohort study, Infectious disease